Analysis Stress Level and Diet for Pregnant Women with The Incidence of Preeclampsia Ahmad Dahlan Hospital - Korbaffo, Anita Restu; Benu, Maria Oktaviana (Universitas STRADA Indonesia, 2019)
Background: Preeclampsia is one of complications in pregnancy happened because increased blood pressure accompanied by proteinuria and edema. This is caused by several factors. Purpose: The purpose of this study to find out the relationship between stress levels and dietary pattern of pregnant women with the incidence of preeklamsia in Hospital Muhammadiyah Ahmad Dahlan Kediri City. Method: The design of this study is correlation with cross sectional. The population studied were all pregnant women who visited the Muhammadiyah Ahmad Dahlan Hospital Kediri City. With gestational age > 20 weeks with a sample of 85 respondents by purposive sampling. Data collection using questionnaires and observation sheets. Data analysis using test chi- square. Result: The results of the study show that pregnant women with moderate stress levels experience as much mild preeclampsia 15 respondent (17,6%) and pregnant women with poor diet who experince as much preeclampsia 13 respondent (15,3%). The result of data analysis show that the variabel stress level p-value (0,088) > ? (0.05) so there is no relationship between stress level and the incidence of preeclampsia whereas for dietary variables p-value (0.029) < ? (0.05) so that Ho rejected and H1 be accepted which means there is a relationship between eating habits and incidence of preeclampsia in the Ahmad Dahlan Hopsital, Kediri city. Conclusion: During pregnancy it is very important for pregnant women to manage stress well and regulate a healthy diet and routinely carry out Antenatal Care.